Model Penilaian Kriteria Bangunan Gedung Hijau Pembangunan Vila Di Kabupaten Badung - I Wayan Muka (Jurnal Permukiman, 2024)
The development of the Bali region is rapidly increasing, particularly the construction of accommodations that support tourism, such as villas and hotels. However, sustainable development has had a negative impact on the environment surrounding projects, including the reduction of green space and accumulation of construction waste. Many of these developments have disregarded government regulations that have been put in place. Construction businesses in Badung Regency are required to implement the concept of Green Building, but there are still numerous obstacles that hinder its implementation. As a result, research was conducted to determine the level of compliance with the Regulation of the Minister of Public Works and Public Housing Number 21 of 2021, the obstacles to implementing Green Buildings, and strategies for overcoming these obstacles. The research method used was a questionnaire distributed to 13 villa projects in Badung Regency, Bali Province, resulting in a total of 39 respondents. The results of the study showed that the implementation of Green Buildings in Badung Regency, Bali Province, has a percentage rate of 64.24% and is classified as being in the middle category of the BGH. The assessment of green building criteria and lack of outreach from the government regarding energy savings and the use of environmentally friendly materials were identified as the main obstacles to implementing Green Buildings